Improving the charge transport of perovskite nanocrystal light-emitting-diodes through Benzylammonium ligand exchange - Minsik Gong; Dong Gyu Lee; Gwang Yong Shin; Yun Seop Shin; Donghwan Yun; Yunhye Jeong; Sang Wook Park; Chan Beom Park; Yung Jin Yoon; Sung Yong Bae; Yun-Hi Kim; Jin Young Kim; et al. (Applied Surface Science Advances)
Lead halide perovskite nanocrystals (LHP NCs) have emerged as promising materials for next-generation display area due to their exceptional luminescence efficiency, size-dependent band gap, and shape control. Ligands on the NC surfaces can be substituted using ligand exchange, which significantly influence the properties and performance of LHP light-emitting diodes (LEDs). The alkyl chain in the surface ligands significantly affect external stimuli depending on their length. Additionally, aromatic ring-containing ligands improve conductivity of the film due to their conjugated structure. Herein, we introduced benzalkonium (BA) to synthesize CsPbBr3 NCs with high quality and explored ligand their optical and electrical properties. The result is that ligand exchange significantly impacts the LHP NCs' characteristics due to overlapped orbitals between the NC surface and π-bonds of the aromatic ring, enhancing charge injection and transport while reducing surface defects. We confirmed the successful anion exchange, which is bound to ammonium ion of BA and the stability of the LHP NCs through various analyses. The modified LHP NCs improved photoluminescence quantum yield and narrower full width at half maximum, indicating improved material purity. This study highlights the potential of ligand exchange to customize LHP NCs’ properties, paving the way for the development of high-efficiency blue LHP LEDs, and other advanced optoelectronic devices. As results, the LHP LEDs using these ligand-exchanged LHP NCs, achieving a notable increase maximum current efficiency (CEmax,) to 5.88 %, 19.5 cd A-1 at BA bromide, and 5.50 %, 16.6 cd A-1 at BA chloride, compared to devices using pristine LHP NCs, which achieved external quantum efficiency (EQE) 2.4 %, CEmax 7.8 cd A-1.